2014
DOI: 10.1002/pssa.201330399
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed gas aggregation for improved nanocluster growth and flux

Abstract: Growth of Cu nanoparticles in a pulsed gas aggregation cluster source was studied. The cluster growth is enhanced by an energy transport inside the aggregation chamber fed by argon that is delivered in short pulses repeated with low frequency. The effect of pressure, varied during the pulse, on the cluster growth was estimated from time‐resolved measurements of mass/size cluster distribution. The cluster mass and the cluster production well correlate with pressure changes. Several stages of cluster growth duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
(38 reference statements)
0
12
1
Order By: Relevance
“…This concept of gas aggregation sources was modified by Haberland et al [13], who substituted evaporation cell by a magnetron, which enabled the production of nanoparticles from materials with high melting point (details related to the GAS may be found in review articles [14][15][16]). These GAS systems were already used for the fabrication of a wide variety of metallic nanoparticles such as for instance Cu, Ti, Ag, and Al [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This concept of gas aggregation sources was modified by Haberland et al [13], who substituted evaporation cell by a magnetron, which enabled the production of nanoparticles from materials with high melting point (details related to the GAS may be found in review articles [14][15][16]). These GAS systems were already used for the fabrication of a wide variety of metallic nanoparticles such as for instance Cu, Ti, Ag, and Al [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For higher pressures, there would be an increased cooling rate of the nanoparticles due to more frequent collisions with the surrounding gas. 9 This would in turn decrease the adatom mobility on the surface of the nanoparticle as well as atomic diffusion on the inside, resulting in an increased polycrystallinity.…”
Section: Crosses Represent Where Oxygen Had To Be Introduced In Ordermentioning
confidence: 99%
“…8 In addition, the sputtering efficiency of magnetron discharges decreases with increasing pressure. 9 This can make it difficult to separate the effect of increasing pressure from a reduction of the sputtering efficiency.…”
mentioning
confidence: 99%
“…However, the instantaneous pressure values in the cluster source varied between = 70 -90 Pa within the pulse period. It is shown that at such conditions the Cu clusters of mass about 10 amu are formed [26].…”
Section: Experimental Arrangementmentioning
confidence: 97%
“…The gas aggregation nanocluster source has been already employed in our previous studies [25], [26] where all necessary details can be found. Hence, only additional pertinent information is provided in this section.…”
Section: Experimental Arrangementmentioning
confidence: 99%